Kamica nerkowa - Metody leczenia u pacjentów geriatrycznych = Urolithiasis - Methods of treatment of geriatric patients - Kamil Radajewski; Izabela Mirlak; Natalia Sokołowska; Remigiusz Sokołowski; Marta Podhorecka; Wojciech Stemplowski; Walery Zukow (Kazimierz Wielki University, 2016)
Radajewski Kamil, Mirlak Izabela, Sokołowska Natalia, Sokołowski Remigiusz, Podhorecka Marta, Stemplowski Wojciech, Zukow Walery. Kamica nerkowa - Metody leczenia u pacjentów geriatrycznych = Urolithiasis - Methods of treatment of geriatric patients. Journal of Education, Health and Sport. 2016;6(8):128-134. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59898 http://ojs.ukw.edu.pl/index.php/johs/article/view/3739       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     Kamica nerkowa - Metody leczenia u pacjentów geriatrycznych Urolithiasis - Methods of treatment of geriatric patients   Kamil Radajewski1, Izabela Mirlak1, Natalia Sokołowska2, Remigiusz Sokołowski2, Marta Podhorecka2, Wojciech Stemplowski2, Walery Zukow3   1Specialist Hospital. Sniadecki in Nowy Sącz, Poland 2Department and Clinic of Geriatrics, Ludwik Rydygier Collegium Medicum in Bydgoszcz NCU, Poland 3WKFZIT, Kazimierz Wielki University, Bydgoszcz, Poland         Słowa klucze: kamica nerkowa, ESWL, PCNL, RIRS, geriatria. Key words: urolithiasis, ESWL, PCNL, RIRS, geriatrics.           Streszczenie   Wstęp. Kamica nerkowa jest to obecność w drogach moczowych nierozpuszczalnych złogów, które powstają w wyniku wytrącania się substancji chemicznych zawartych w moczu, gdy ich stężenie przekracza próg rozpuszczalności. Największy wzrost zachorowań obserwowany jest w przedziale wiekowym 60-74 lata. Coraz częściej w leczeniu kamicy stosowane są mało inwazyjne metody leczenia, wśród których wyróżniamy przezskórną nefrolitotrypsję, litotrypsję zewnątrzustrojową falą uderzeniową, oraz wsteczną ureterorenoskopię giętką. Cel. Porównanie mało inwazyjnych metod leczenia kamicy moczowej u pacjentów geriatrycznych. Materiały i metody. Posługując się słowami kluczowymi przeszukano zagraniczne bazy bibliograficze: Embase, Medline, ScienceDirect, Web of Sciense. Przeanalizowano badanie kliniczne opublikowane w języku angielskim i międzynarodowych czasopismach. Wyniki. Najczęściej stosowaną metodą leczenia u pacjentów geriatrycznych jest itotrypsja zewnątrzustrojową falą uderzeniową. Na wybór metody wpływa nie tylko wielkość kamienia ale również choroby współistniejące takie jak cukrzyca, nadciśnienie tętnicze, niewydolność nerek. Wnioski. Z przeprowadzonych dotychczas badań wynika, że sam wiek nie jest czynnikiem determinującym wybór metody. Jakkolwiek, wciąż potrzeba dalszych badań w grupie pacjentów geriatrycznych, aby zmniejszyć liczbę powikłań po leczeniu inwazyjnym kamicy nerkowej.       Summary   Admission. Urolithiasis is present in the urinary insoluble deposits, which result from precipitation chemicals in the urine when their concentration exceeds the limit of solubility. The highest increase in incidence is observed in the age group 60-74 years. More and more frequently in the treatment of urolithiasis are used in minimally invasive treatments, among which we distinguish percutaneous nephronlithotripsy, lithotripsy extracorporeal shock wave and backward ureterorenoscopy flexible. Objective. Comparison of minimally invasive treatment of urolithiasis geriatric patients. Materials and methods. Using the keywords searched international bibliographic databases: Embase, Medline, Science Direct, Web of Science. We analyzed clinical trial published in English and international journals. Results. The most commonly used treatment for geriatric patients is extracorporeal shock wave lithotripsy. The choice of the method is affected not only the size but also stone co-morbidities such as diabetes, hypertension, renal failure. Conclusions. From the studies to date show that age alone is not the determining factor in the choice of method. However, we still need further research in geriatric patients, to reduce the number of complications after invasive treatment urolithiasis.